The Impact of Electronic Health Records on Workflow and Financial Measures in Primary Care Practices. (21st December 2013) - Fleming, Neil S.; Becker, Edmund R.; Culler, Steven D.; Cheng, Dunlei; McCorkle, Russell; Graca, Briget da; Ballard, David J.
Abstract : Objective: To estimate a commercially available ambulatory electronic health record's (EHR's) impact on workflow and financial measures. Data Sources/Study Setting: Administrative, payroll, and billing data were collected for 26 primary care practices in a fee‐for‐service network that rolled out an EHR on a staggered schedule from June 2006 through December 2008. Study Design: An interrupted time series design was used. Staffing, visit intensity, productivity, volume, practice expense, payments received, and net income data were collected monthly for 2004–2009. Changes were evaluated 1–6, 7–12, and >12 months postimplementation. Data Collection/Extraction Methods: Data were accessed through a SQLserver database, transformed into SAS ®, and aggregated by practice. Practice‐level data were divided by full‐time physician equivalents for comparisons across practices by month. Principal Findings: Staffing and practice expenses increased following EHR implementation (3 and 6 percent after 12 months). Productivity, volume, and net income decreased initially but recovered to/close to preimplementation levels after 12 months. Visit intensity did not change significantly, and a secular trend offset the decrease in payments received. Conclusions: Expenses increased and productivity decreased following EHR implementation, but not as much or as persistently as might be expected. Longer term effects still need to be examined.